Liquidity Risk and Bank Performance: Empirical Evidence from Chinese Commercial Banks - Li, Wangyang (2022)
Liquidity risk is been attached more importance after the 2008 financial crisis. Unforeseen events that happened in recent years impacted the liquidity of Chinese commercial banks, furtherly posing a threat to bank performance. This paper focuses on the relationship between liquidity risk and bank performance. Liquidity coverage ratio (LCR), liquid assets to total assets (LATA), liquidity ratio (LR), loan to deposit ratio (LTD) and cash to total assets ratio (CTA) are proxies for liquidity risk. Bank performances are measured by NIM, ROAA and ROAE respectively. The dataset consists of 16 representative Chinese commercial banks from 2012 to 2021, and the two-way fixed effect model is adopted in this study. It is found that the selected liquidity variables have different impacts on them. Firstly, LCR and LTD are negatively significant in determining NIM and ROAE respectively from a statistical view. Secondly, LATA has a significant and positive relationship with NIM and ROAE, while a significantly negative relationship is found only between CTA and NIM. Thirdly, all the selected liquidity risk variables do not have an impact on ROAA, but it is influenced by the first order lag of LCR and LTD. The empirical results may provide some guidance for the staff in Chinese commercial banks on how to maintain a balance between liquidity risk and bank performance.